Intravenous anaesthesia using detomidine, ketamine and guaiphenesin for laparotomy in pregnant pony mares - Taylor, Polly M.; Luna, Stelio P. L. [UNESP]; White, Kate L.; Bloomfield, Malcolm; Fowden, Abigail L. (Elsevier, 2001)
Objective To characterize intravenous anaesthesia with detomidine, ketamine and guaiphenesin in pregnant ponies. Animals Twelve pony mares, at 260–320days gestation undergoing abdominal surgery to implant fetal and maternal vascular catheters. Materials and methods Pre-anaesthetic medication with intravenous (IV) acepromazine (30µgkg−1), butorphanol (20µgkg−1) and detomidine (10µgkg−1) preceded induction of anaesthesia with detomidine (10µgkg−1) and ketamine (2mgkg−1) IV Maternal arterial blood pressure was measured directly throughout anaesthesia and arterial blood samples were taken at 20-minute intervals for measurement of blood gases and plasma concentrations of cortisol, glucose and lactate. Anaesthesia was maintained with an IV infusion of detomidine (0.04mgmL−1), ketamine (4mgmL−1) and guaiphenesin (100mgmL−1) (DKG) for 140minutes. Oxygen was supplied by intermittent positive pressure ventilation (IPPV) adjusted to maintain PaCO2 between 5.0 and 6.0kPa (38 and 45mmHg), while PaO2 was kept close to 20.0kPa (150mmHg) by adding nitrous oxide. Simultaneous fetal and maternal blood samples were withdrawn at 90minutes. Recovery quality was assessed. Results DKG was infused at 0.67±0.17mLkg−1 hour−1 for 1hour then reduced, reaching 0.28±0.14mLkg−1hour−1 at 140minutes. Arterial blood gas values and pH remained within intended limits. During anaesthesia there was no change in heart rate, but arterial blood pressure decreased by 10%. Plasma glucose and lactate increased (10-fold and 2-fold, respectively) and cortisol decreased by 50% during anaesthesia. Fetal umbilical venous pH, PO2 and PCO2 were 7.34±0.06, 5.8±0.9kPa (44±7mmHg) and 6.7±0.8kPa (50±6mmHg); and fetal arterial pH, PO2 and PCO2 were 7.29±0.06, 4.0±0.7kPa (30±5mmHg) and 7.8±1.7kPa (59±13mmHg), respectively. Surgical conditions were good but four ponies required a single additional dose of ketamine. Ponies took 60±28minutes to stand and recovery was good. Conclusions and clinical relevance Anaesthesia produced with DKG was smooth while cardiovascular function in mare and fetus was well preserved. This indicates that DKG infusion is suitable for maintenance of anaesthesia in pregnant equidae. © 2017 Wiley. All rights reserved.
Keywords: Anaesthesia; Detomidine; Guaiphenesin; Ketamine; Ponies; Pregnancy